Makna Verba Bahasa Jepang “Tsukuru” Dan Bahasa Indonesia “Membuat” - Sri Wahyu Istana Trahutami (KIRYOKU, 2021)
(Verb Means "to make" in Japanese and Indonesian). The number of Japanese vocabularies which is much more than Indonesian often causes problems when learning Japanese. One of the difficulties that are often faced is understanding the meaning and finding its equivalent in Indonesian. The purpose of writing this article is to describe the meaning of the verb tsukuru in Japanese, and the verb to make in Indonesian while looking for similarities and differences in the meanings of the two verbs. Research data was obtained from articles and websites. The qualitative descriptive method was used to analyze the data of Japanese and Indonesian sentences, followed by analyzing the similarities and differences in their meanings through comparisons (contrastive). Based on the results of the analysis, it is concluded that both verbs function as predicates intransitive sentences. Both are also polysemy with the basic meaning of creating objects or things that did not exist before, using the abilities possessed by the maker. While the difference is, the verb to make in Indonesian also has the meaning of causing. Meanwhile, in Japanese, the verb tsukuru means not only to make but also to maintain, to care for, to educate. In addition, there are three different letters for the verb tsukuru, each of which has a different pair of objects